MANUFACTURE OF SOLAR DIRTY WATER RECYCLING TOOL USING FLAT PLATE COLLECTOR - Egi Yuliora; Rajabal Akbar (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The astromi indonesia traversed a line equator Provides the potential for maximum solar energy, this energy source be used to recycle water. Indonesia as a country maritime had area of water 62,89% from area of Indonesia, but this fact does not guarantee the large number of clean water supplies in each region. The instrument recycle water with solar energy designed to produce clean water be used solar radiation absorbed by flat plate collector will Help the process of evaporation dirty water A container at the top of a collector, So that will yield water vapor and the condensed form the grain of the water (condensate) On the surface of cover collector, so Of the water where they cleansed and pruned already can be funneled into a clean water storage. The rate of volume clean water every hour is 217,5 ml with temperature 37,2oC and The intensity of sunlight on cover collector is 350 Cd. This clean water can not be consumed by body and Need to processed further by a chemical process.